2000
DOI: 10.1021/om0001523
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation and Full Characterization of 2,2‘-Bishalosilyl-Substituted 1,1‘-Binaphthyls:  Synthesis of 2,2‘-Bis(fluorodimethylsilyl)-1,1‘-binaphthyl and X-ray Structural Analysis of Highly Strained Disilanylene-Bridged Precursors

Abstract: Brominative Si-Si cleavage of 3,4-disila-3,3,4,4-tetramethyl-3,4-dihydrodibenzo[c,g]phenanthrene (3a), LiAlH 4 reduction of the resulting dibromide, and fluorination of the dihydride 14a thus gave 2,2′-bis(fluorodimethylsilyl)-1,1′-binaphthyl (7a) in high yield as the first isolated and fully characterized 2,2′-bis(halosilyl)-1,1′-binaphthyl. Similar conversion of the more sterically hindered 3,4-disila-3,3-dimethyl-4,4-diphenyl-3,4-dihydrodibenzo[c,g]phenanthrene (3b) also gave the corresponding bishydrosilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In 2000, highly strained rings 71 and 72 consisting of a disilane linker and binaphthyl were synthesized. 115 The crystal structure revealed that the silicon atom is substantially deformed from the tetrahedral geometry. Take 71 as an example, the Si–Si–C(methyl) bond angle is enlarged to 119.0°.…”
Section: Disilane-bridged Chromophoresmentioning
confidence: 99%
“…In 2000, highly strained rings 71 and 72 consisting of a disilane linker and binaphthyl were synthesized. 115 The crystal structure revealed that the silicon atom is substantially deformed from the tetrahedral geometry. Take 71 as an example, the Si–Si–C(methyl) bond angle is enlarged to 119.0°.…”
Section: Disilane-bridged Chromophoresmentioning
confidence: 99%
“…In the solid state, perarylated siloles exhibit high luminescent properties owing to restricted rotation of the aromatic rings . The luminescent properties of the siloles were attributed to their low LUMO level caused by conjugation of σ*(Si) and π*(diene) orbitals. , 1,2-Disilacyclohexadienes with a six-membered ring composed of two CC bonds and an Si–Si bond were reported to possess nonplanar ring structures. , Marder et al compared the electronic state and luminescent behavior of the siloles and 1,1,2,2-tetramethyl-3,4,5,6-tetraphenyl-1,2-disila-3,5-cyclohexadiene . Acyclic disilanes with π-conjugated substituents also show unique luminescent properties based on the intramolecular charge-transfer mechanism between the Si–Si σ bonds and π orbitals of CC bonds or aromatic rings. Similar intramolecular charge transfer from the disilanylene unit was also proposed for disilanylene-bridged silafluorene with a rigid planar structure, which emitted at a longer wavelength in the solid state .…”
Section: Introductionmentioning
confidence: 99%